ADSCs enhance VEGFR3-mediated lymphangiogenesis via METTL3-mediated VEGF-C m6A modification to improve wound healing of diabetic foot ulcers - Jie Zhou; Tianhong Wei; Zhiyou He (BMC, 2021)
Abstract Background Adipose-derived mesenchymal stem cells (ADSCs) are an important focus in regenerative medicine. However, the biological function of ADSCs in the wound repair of diabetic foot ulcers (DFUs) remains unclear. This study aimed to determine the underlying mechanisms of ADSCs involved in the wound healing of DFUs. Methods The cell surface markers cluster of differentiation 34 (CD34), stromal cell antigen 1 (Stro-1), cluster of differentiation 90 (CD90) and cluster of differentiation 105 (CD105) on ADSCs were identified by flow cytometry. Oil Red O staining and Alizarin Red S staining were performed to identify the multipotential differentiation of ADSCs into adipocytes and bone. The levels of Methyltransferase-like 3 (METTL3), vascular endothelial growth factor C (VEGF-C) and insulin-like growth factor 2 binding protein 2 (IGF2BP2) were assessed by RT-qPCR. CCK-8, Transwell and tubule formation assays were conducted to assess lymphatic endothelial cell (LEC) viability, migration and tubule formation ability, respectively. RIP and RNA pulldown assays were conducted to assess the interaction between IGF2BP2 and VEGF-C. The levels of VEGF-C, VEGFR3, LYVE-1 and IGF2BP2 proteins were assessed by Western blotting. The levels of VEGF-C in LECs were measured by ELISA. Results Our findings illustrated that ADSCs accelerate LEC proliferation, migration and lymphangiogenesis via the METTL3 pathway and regulate VEGF-C expression via the METTL3/IGF2BP2-m6A pathway VEGF-C-mediated lymphangiogenesis via the METTL3/IGF2BP2-m6A pathway in DFU mice. Conclusion ADSCs enhance VEGFR3-mediated lymphangiogenesis via METTL3-mediated VEGF-C m6A modification to improve wound healing in DFUs, indicating that ADSCs may be regarded as a promising therapeutic strategy to promote wound healing in DFUs.